2018
DOI: 10.1016/j.juro.2017.07.082
|View full text |Cite
|
Sign up to set email alerts
|

5′-tRNA Halves are Dysregulated in Clear Cell Renal Cell Carcinoma

Abstract: In patients with clear cell renal cell carcinoma 5'-tRNA halves have potential as diagnostic and prognostic biomarkers. The 5'-tRNA halves may act in a tumor suppressive manner, which requires further research to confirm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…tsRNAs take part in cellular processes including cell proliferation (12,31), metastasis (32) and apoptosis (32,33). Diagnostic potential of tsRNAs was also reported in prostate cancer (34), liver cancer (8) and clear cell renal cell carcinoma (23). Although the function of tsRNAs remains largely unknown in cancer process, but they may be suitable as cancer biomarkers (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tsRNAs take part in cellular processes including cell proliferation (12,31), metastasis (32) and apoptosis (32,33). Diagnostic potential of tsRNAs was also reported in prostate cancer (34), liver cancer (8) and clear cell renal cell carcinoma (23). Although the function of tsRNAs remains largely unknown in cancer process, but they may be suitable as cancer biomarkers (35).…”
Section: Discussionmentioning
confidence: 99%
“…In order to measure tsRNAs levels in each sample, tsRNAs were ampli ed selectively without full-length tRNA quanti cation by existing protocol (23,24). The serum or tissue RNA was poly-A tailed using E. coli Poly(A) Polymerase (NEB, M0276) for 30 minutes at 37 °C followed by 10 minutes at 65 °C.…”
Section: Tsrnas Quanti Cationmentioning
confidence: 99%
“…The tRNA halves have been associated with diseases ( Honda et al, 2015 ; Nientiedt et al, 2016 ; Zhao et al, 2018 ). Angiogenin is a ribonuclease that under stress conditions cleaves tRNA at the anticodon loop, producing tRNA-derived fragments, including tRNA halves ( Ivanov et al, 2011 ; Saikia et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to believe that tsRNA is a new target for tumor therapy. Besides, tsRNAs can be detected in the urine and serum from tumor patients [ 69 , 70 , 71 ], suggesting they can be used as molecular markers for tumor diagnosis. For example, Dhahbi et al found that the level of tsRNAs in the blood samples from breast cancer patients was closely related to the pathological characteristics through small RNA high-throughput sequencing analysis [ 72 ]; Honda et al found that a kind of hormone dependent tsRNA was abundant in breast cancer and prostate cancer and can enhance the proliferation of cancer cells [ 16 ].…”
Section: Roles Of Trna-derived Small Rna In Diseasesmentioning
confidence: 99%